Mengungkap Kualitas Lembaga Pendidikan Anak Usia Dini: Tinjauan Peran Kepala Sekolah - Nawangwulan, Andina Wahyu; Aisiyah, Laily Nur; Haidlor, Muhammad (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
The quality of education can be measured by the role of the principal. This study aims to describe the role of the principal in the quality of education at TK Arni Jember. The method used is a descriptive method in the form of spoken and written words from the subject of the perpetrators observed using a qualitative approach. Data collection techniques used are observation, interview and documentation techniques. The subjects of this study consisted of the principal and teachers at TK Arni Jember. Data analysis of the study used a model developed by Milles and Huberman. The results of this study explain that the quality of education at TK Arni Jember has met the National Education Standards and the role of the principal in improving the quality of education in the institution has been running well. This can be seen in terms of the quality of education and work programs that have been implemented well from time to time. The principal as a leader always outlines the school's vision and mission to achieve quality targets, involves teachers and parents in school decision-making, always provides innovation, motivation and work enthusiasm to all educators and education staff so that they remain enthusiastic in carrying out their duties to continue to improve the quality of education at TK Arni Jember.